Group A Streptococcal Toxic Shock Syndrome after a Routine Gynecological Procedure - Kei Ameda; Yoko Yamada; Yuriko Uehara; Tamami Ohno; Mari Hoya; Hiroko Oda; Misako Mishima (Case Reports in Obstetrics and Gynecology)
Streptococcal toxic shock syndrome (STSS) is a life-threatening illness mainly caused by invasive group A Streptococcus (GAS) infection. Herein, we report a case of a postmenopausal woman who developed STSS from an ascending vaginal GAS infection after cytocervical sampling. The patient complained of vaginal discharge, for which she underwent gynecological examination with vaginal sampling. The following day, there was onset of diarrhea and vomiting. After 7 days, she was admitted to our hospital with septic shock. Necrotizing enterocolitis was suspected and surgical intervention was performed; however, the patient was diagnosed with primary peritonitis and antibiotics were initiated. On day 2, GAS was suspected by blood cultures, and antibiotics were changed in consideration of STSS. On day 4, GAS was confirmed in blood, ascitic fluid, and vaginal swab specimens, and STSS caused by an ascending vaginal GAS infection was diagnosed. This case report indicates that STSS could occur following cytocervical sampling for vaginal discharge. If a woman has unexplained septic shock, especially with gastroenteritis symptoms, STSS should be considered as a differential diagnosis.